St. John's wort extract and hyperforin inhibit multiple phosphorylation steps of cytokine signaling and prevent inflammatory and apoptotic gene induction in pancreatic β cells. (December 2016) - Novelli, Michela; Menegazzi, Marta; Beffy, Pascale; Porozov, Svetlana; Gregorelli, Alex; Giacopelli, Daniela; De Tata, Vincenzo; Masiello, Pellegrino
Graphical abstract: Highlights: St. John's wort extract (SJW) and hyperforin (HPF) block cytokine effects in β cells. SJW and HPF simultaneously inhibit cytokine-induced STAT-1, NF-κB and MAPK activation. SJW and HPF hinder multiple phosphorylation steps of signaling pathways. SJW and HPF prevent induction of inflammatory and apoptotic cytokine target genes. These natural compounds are exploitable for prevention of immune-mediated β-cell loss. Abstract: The extract of the herbaceous plant St. John's wort (SJW) and its phloroglucinol component hyperforin (HPF) were previously shown to inhibit cytokine-induced STAT-1 and NF-κB activation and prevent damage in pancreatic β cells. To further clarify the mechanisms underlying their protective effects, we evaluated the phosphorylation state of various factors of cytokine signaling pathways and the expression of target genes involved in β-cell function, inflammatory response and apoptosis induction. In the INS-1E β-cell line, exposed to a cytokine mixture with/without SJW extract (2–5 μg/ml) or HPF (1–5 μM), protein phosphorylation was assessed by western blotting and expression of target genes by real-time quantitative PCR. SJW and HPF markedly inhibited, in a dose-dependent manner (from 60 to 100%), cytokine-induced activating phosphorylations of STAT-1, NF-κB p65 subunit and IKK (NF-κB inhibitory subunit IκBα kinase). MAPK and Akt pathways were also modulated by the vegetal compounds through hindrance of p38 MAPK, ERK1/2, JNK and Akt phosphorylations, each reduced by at least 65% up to 100% at the higher dose. Consistently, SJW and HPF a) abolished cytokine-induced mRNA expression of pro-inflammatory genes; b) avoided down-regulation of relevant β-cell functional/differentiation genes; c) corrected cytokine-driven imbalance between pro- and anti-apoptotic factors, by fully preventing up-regulation of pro-apoptotic genes and preserving expression or function of anti-apoptotic Bcl-2 family members; d) protected INS-1E cells against cytokine-induced apoptosis. In conclusion, SJW extract and HPF exert their protective effects through simultaneous inhibition of multiple phosphorylation steps along various cytokine signaling pathways and consequent restriction of inflammatory and apoptotic gene expression. Thus, they have a promising therapeutic potential for the prevention or limitation of immune-mediated β-cell dysfunction and damage leading to type 1 diabetes.